Growth analysis in the potato crop under different irrigation levels - Netto, ADA; Rodrigues, J. D.; De Pinho, S. Z. (Empresa Brasil Pesq Agropec, 2000)
An experiment was carried out at Fazenda Sao Manoel, pertaining to the Faculdade de Ciencias Agronamicas of the Universidade Estadual Paulista, Sao Manuel, SP, Brazil, to evaluate irrigation levels in the potato (Solanum tuberosum ssp, tuberosum) growth, cv. Aracy. This work was installed in a Bandy Dark-Red Latosol, under a plastic cover. The experimental design was an entirely randomized block composed by irrigation in the potato plots when the soil water potential has reached 15, 35, 55, 75 and 1,500 kPa,and five plant sampling time with four replicates. It was found that higher irrigation levels led to increase of the leaf area index, leaf area duration, relative growth rate and net assimilation rate.
Keywords: leaf area index; relative growth rate; net assimilation rate